2016
DOI: 10.5194/isprs-archives-xlii-4-w1-9-2016
|View full text |Cite
|
Sign up to set email alerts
|

Identifying High-Risk Populations of Tuberculosis Using Environmental Factors and Gis Based Multi-Criteria Decision Making Method

Abstract: ABSTRACT:Development of an innovative method to enhance the detection of tuberculosis (TB) in Malaysia is the latest agenda of the Ministry of Health. Therefore, a geographical information system (GIS) based index model is proposed as an alternative method for defining potential high-risk areas of local TB cases at Section U19, Shah Alam. It is adopted a spatial multi-criteria decision making (MCDM) method for ranking environmental risk factors of the disease in a standardised five-score scale. Scale 1 and 5 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The five-score scale is calculated from the combination values from the expert's opinion, existing theories, and previous studies. The scale of 1 to 5 shows the lowest and the highest level of risk area, respectively as studied by Abdul Rasam et al, (2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The five-score scale is calculated from the combination values from the expert's opinion, existing theories, and previous studies. The scale of 1 to 5 shows the lowest and the highest level of risk area, respectively as studied by Abdul Rasam et al, (2016).…”
Section: Methodsmentioning
confidence: 99%
“…A GIS can produce maps of the exposure and disease to reveal spatial patterns and predict the complex phenomena. Previous studies have practically proven that the technology can be used in TB epidemiological management, disease mapping, risk assessment and spread prediction (Abdul Rasam et al, 2016;Carroll et al, 2014;Li et al, 2014;Pfeiffer & Stevens, 2010;Zhao et al, 2013, Rasam et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that human factors are the main factors in Shah Alam instead of ecological factors, especially the number of population (housing or localities), risk group or low income, and TB mobility which require empirical proof. However, the combination of ecological risk factors such as urban area, type of house, healthcare distance may increase the risk factor in an area (Liu et al, 2011;Zhao et al, 2013;Abdul Rasam et al, 2016). This finding is important for the model development process and to enhance the understanding of the local health staff in explaining the TB dynamics.…”
Section: Figure 1 Spatial Clustering and Risk Areas Of Tb Cases In Smentioning
confidence: 99%
“…Previous studies have shown the environmental risk factors in high burden countries of TB can be divided into two main indicators, including ecological environment, human or social environment. The ecological environment is another term of the environment, relating the biotic and abiotic surrounding of an organism or population, For example, TB high-risk prevalence areas are co-impacted by spatial proximity or geographical factor [1][2] [12] especially in urban area [1] [12][3] [38], poor housing quality, crowded and small living condition [14]. Low SES also contributes to the global TB occurrences [2][12] such as unemployment, low educational level and poverty.…”
Section: Introductionmentioning
confidence: 99%